The effect of familiarity on older adults’ engagement in exergames - Zhang, Hao (2020)
With entertaining game graphics and tasks, exergames can provide benefits for older adults to effectively exercise their physical and mental capabilities. However, it is sometimes difficult for exergames to engage older adults due to maladaptation. In this work, we suggest that the feeling of familiarity can positively influence older adult’s adaptation to exergames. Based on this intuition, to help exercise older adult’s upper limbs, we design a Ping Pong Exergame (PPE) infused with table tennis activities, which has been shown to be one of the most popular (thus familiar) sports among Singaporean older adults. A five-week study involving 44 Singaporean older adults shows that the participants who have higher levels of familiarity to table tennis exhibit higher motivation and ability in playing PPE, which indicate that familiarity can improve older adults’ adaptation to exergames.